TUC Secretaries General (2013)
2013 1960-2000 "TUC Secretaries General" [T0626], 2013 Four Secretaries General of the TUC (l-r): John Monks (1993-2003), Norman Willis (1984-1993), Frances O'Grady (2014-), Brendan Barber (2003-2013). Photographed at a function at Congress House, 2013.